HILDA Project Discussion Paper Series Wave 20 data quality and the impact of questionnaire and fieldwork changes due to the COVID-19 pandemic - Watson, Nicole; Jin, Yihua; Summerfield, Michelle (My University, 2021)
This paper describes the various changes made to the administration of wave 20 and then compares the quality of the data with the previous two waves. The aspects of data quality examined include response rates, response timing, missing data, use of multi-item response options, responses chosen for questions with long response lists, straight lining, rounding, and the length of responses provided at open-ended questions.
HILDA Project Discussion Papers
Keywords: Surveys and survey methodology